Sobre los huesos de los muertos - Tokarczuk, Olga, 1962- (Nuevos tiempos (Madrid, Spain), 2016)
The actions of this crime novel occur in a mountainous province of Poland. It stars Janina Duszejko, a retired woman who attempts to solve the murders of several hunters. The author questions both the level of disrespect man holds to nature as well as the dangers of environmental radicalism, however good their intentions.